2005
DOI: 10.1111/j.1365-2036.2005.02440.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different organic acids (citric, malic and ascorbic) on intragastric urease activity

Abstract: SUMMARYBackground: The mechanism of citric acid-enhanced Helicobacter pylori urease activity remains unclear. Aim: To compare ascorbic, citric and malic acid given at the same concentration and pH on intragastric urease activity. Methods: Volunteers received 40 mg of famotidine the evening prior to breath testing. After an overnight fast volunteers were randomized to receive 100 mL of water or 100 mm citric, malic, or ascorbic acid, pH 2.3 containing 75 mg of 13 C-urea. At 15 min a second

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Studies are needed that control pH in patients who receive bismuth after administration of a PPI or a potassium-competitive acid blocker to better understand the effects of bismuth relation to pH in vivo. If an acidic stomach is required for full effectiveness (eg, to generate bismuth oxychloride), options might include administering the bismuth salt with citric acid, malic acid or even Coca Cola to temporarily acidify the stomach,82 or administering bismuth oxychloride tablets.…”
Section: Understanding the Variation In Outcome With Triple Therapy Pmentioning
confidence: 99%
“…Studies are needed that control pH in patients who receive bismuth after administration of a PPI or a potassium-competitive acid blocker to better understand the effects of bismuth relation to pH in vivo. If an acidic stomach is required for full effectiveness (eg, to generate bismuth oxychloride), options might include administering the bismuth salt with citric acid, malic acid or even Coca Cola to temporarily acidify the stomach,82 or administering bismuth oxychloride tablets.…”
Section: Understanding the Variation In Outcome With Triple Therapy Pmentioning
confidence: 99%
“…A Czech study conducted on healthy volunteers revealed that a citric acid solution as a test drink was superior to orange juice and water, and the optimal time intervals for breath sampling were 20 or 25 minutes after urea ingestion [2]. Another study demonstrated that, in contrast to ascorbic acid, citric acid and malic acid had the same enhancing effect on intragastric urease activity, so malic acid could replace citric acid as a test meal in the 13 C‐UBT [3]. A study on the performance of the 14 C‐urea breath test comparing citric acid, trisodium citrate, and drinking water as test meals showed that a small amount of citric acid (1.3 g) with only one breath sampling between 15 and 30 minutes after urea ingestion was sufficient to diagnose H. pylori infection accurately [4].…”
Section: Non‐invasive Testsmentioning
confidence: 99%
“…As a result, different mechanisms of AA interactions with urease were hypothesized, including DHA-modification of the protein 24,33,36 , AA-reduction of Ni 2+ ions in the urease active site 25,36 , some reactions resulting from the reduction of Cu 2+ by AA 35 , and finally the reactions of Cu 2+ and Cu + with urease 34,35 . In this work, we showed that in the unbuffered system AA inactivated urease by denaturation brought about by AA-lowered pH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that high doses of vitamin C afforded to reduce colonization of the bacterium in the gastric mucosa 21 or even to eradicate the bacterium 22 . AA was also shown in vitro to inhibit Helicobacter pylori growth 23 and urease activity 24 , the latter hypothetically by reducing Ni 2+ ions in the enzyme active site 25 . Noteworthily, it has now been estimated that at least half the world's population are infected with Helicobacter pylori.…”
Section: Urease Activity and L-ascorbic Acidmentioning
confidence: 99%